Comparative Study of Plywood Boards Produced with Castor Oil-Based Polyurethane and Phenol-Formaldehyde Using Pinus taeda L. Veneers Treated with Chromated Copper Arsenate - Sugahara, Estefani [UNESP]; Casagrande, Bruno [UNESP]; Arroyo, Felipe; Araujo, Victor de; Santos, Herisson; Faustino, Emerson; Christoforo, Andre; Campos, Cristiane [UNESP] (MDPI, 2022)
Plywood is widely used in civil construction. Due to the importance of preservation and gluing in bio-composites, this study compares the influence of a chemical treatment with CCA (chromated-copper-arsenate) on Pinus taeda L. wood veneers to produce two plywood types using phenol-formaldehyde (PF) and castor oil-based polyurethane (PU). Four different treatments were performed to analyze both varieties’ physical and mechanical properties. As a result, an improvement in the properties of the treated panels was observed. Lower moisture contents and better interactions caused by less thickness swelling and water absorption were identified in the PU-based plywoods. The treatment with CCA was efficient, improving these properties when they were compared to the reference panels. Most treatments evidenced increases in the modulus of elasticity and modulus of rupture for both adhesives when the CCA treatment was applied to the veneers. Comparing the resins, the PF showed the best values of modulus of elasticity. All treatments met the requirements defined by the Brazilian standard document for the glue line shear.
Keywords: bio-composite; castor oil-based polyuretane; chromated-copper-arsenate; phenol-formaldehyde; physical and mechanical properties; Pinus taeda